Epidemiology and aetiology of maternal parasitic infections in low- and middle-income countries - Roberts, Tom; Gravett, Courtney A; Velu, Prasad Palani; Theodoratou, Evropi; Wagner, Thor A; Zhang, Jian Shayne F; Campbell, Harry; Rubens, Craig E; Gravett, Michael G; Rudan, Igor (Journal of global health, 2011)
There have been very few systematic reviews looking at maternal infections in the developing world, even though cutting maternal mortality by three quarters is United Nation's Millennium Development Goal number five. This systematic review has two aims. The first is to present the prevalence of parasitic infections in the developing world over the last 30 years and the second is to evaluate the quality and distribution of research in this field. A systematic review of Medline, EMBASE and Global Health databases was undertaken using pre-determined search criteria. Three levels of quality criteria for exclusion of inadequate studies identified 115 out of initial 8580 titles. The data were extracted for 5 domains: worldwide pathogen prevalence, year of study, study setting, sample size and diagnostic test for each pathogen. The initial search retrieved 8580 results. From these titles, 43 studies on malaria, 12 studies on helminths, 49 studies on Toxoplasma gondii, 7 studies on Chagas disease, 5 studies on Trichomonas, 1 leishmaniasis study and 1 study on trichinellosis were extracted for analysis. High prevalence of malaria was found in Gabon (up to 57%) India (55%), Cameroon (50%), Yemen (55%), Nigeria (up to 64%) and Ghana (54%). High prevalence of hookworm infections was found in Nepal at 78.8% and high values of Ascaris lumbricoides were found in Nepal, (56.2%), Kenya (52.3%) and Gabon (45.5%). High levels of Schistosoma mansoni were found in Zimbabwe (50%) and Tanzania (63.5%). The prevalence of active Toxoplasma gondii infection was found to be highest in India (27.7%). This study highlights the large burden of maternal parasitic infections globally. It may serve as a useful starting point for health policy development and research prioritization in this area.